Moving from a Textual to Visual Medium: Transposition of Ruskin Bond’s The Blue Umbrella to the Cinematic Canvas (Literary Voice, 2024)
Intertextuality, which emphasizes the interaction of various works of art, is associated with adaptation studies. According to comparative literature scholar James Naremore, modern life's nerve center is remaking. Additionally, based on the interpretation of the original source material, remaking brings out ideological and aesthetic beliefs. According to the intertextuality school of thought, the novel always comes before the movie, but a consumer is more likely to see the movie first. However, the novel and the movie complement one another visually and aesthetically due to the components they contain. The study attempts to explore how Vishal Bharadwaj's adaptation of Ruskin Bond's novella The Blue Umbrella differs from the original and how they stay connected. The paper will try to find aspects of film and literature that are not easily changeable while considering the convergence of these two art forms.
Keywords: Intertextuality, Adaptation, Convergence, Fidelity, Aesthetics